A thermal self-healing polyurethane thermoset based on phenolic urethane - Cao, Shan; Li, Shouhai; Li, Mei; Xu, Lina; Ding, Haiyang; Xia, Jianling; Zhang, Meng; Huang, Kun (Polymer journal, 2017)
Thermosetting polyurethanes have excellent elastic properties and solvent resistance, but they cannot be reshaped like thermoplastic polymers after molding. In this study, we designed a thermosetting polyurethane based on a reversible reaction between isocyanates and phenolic hydroxyls instead of alcoholic hydroxyls. The phenolic urethane partially decomposed above 120 °C, but the phenolic hydroxyl and isocyanate groups reconnected upon cooling. These reversible urethane bonds contributed to the thermal self-repair of the thermosetting polyurethane network. This thermosetting elastomer was organic-insoluble below 120 °C. Compared to the original material, the healed thermoset preserved approximately 70% of its tensile strength and exhibited 86% elongation at break. This thermosetting polyurethane can be applied in self-healing coatings or adhesives. We designed a thermosetting polyurethane based on the reversible reaction between isocyanates and phenolic hydroxyls instead of alcoholic hydroxyls. The phenolic urethane partially decomposed at above 120 °C, but the phenolic hydroxyl and isocyanate reconnected upon cooling. This reversible urethane bond contributed to the thermal self-repair of the thermosetting polyurethane network and can be applied into self-healing coatings or adhesives.